Social Welfare in India - S, Sadhasivam (Recent Research Reviews Journal, 2023)
In spite of social issues like destitution, financial inequality, etc., developing countries like India strive to have unprecedented economic growth. India has two different social welfare sectors. One is formal or organized and another one is informal or unorganized sector. The organized sector is run directly by the government, state-owned businesses, and private companies. It offers their workers a fair amount of social protection through mandatory laws covering certain things. The unorganized sector is covered by a defective network of social welfare and benefits offered by the national government of a federation and the relevant state governments. This article describes the constitutional position of welfare in India along with an outline of its historical development. With regard to the unorganized sector of the economy, it offers a summary of some major promotions and safety-oriented welfare programs and policies, including those that deal with problems like unemployment, health, education, and poverty. Further, it discusses the history and evolution of central and respective state governments in social welfare, the goals and nature of social welfare, and social welfare schemes.